The role of electroencephalography in epilepsy research-From seizures to interictal activity and comorbidities - Lisgaras, Christos Panagiotis; de la Prida, Liset M; Bertram, Edward; Cunningham, Mark; Henshall, David; Liu, Anli A; Gnatkovsky, Vadym; Balestrini, Simona; de Curtis, Marco; Galanopoulou, Aristea S; Jacobs, Julia; Jefferys, John G R; et al. (Epilepsia, 2025)
Electroencephalography (EEG) has been instrumental in epilepsy research for the past century, both for basic and translational studies. Its contributions have advanced our understanding of epilepsy, shedding light on the pathophysiology and functional organization of epileptic networks, and the mechanisms underlying seizures. Here we re-examine the historical significance, ongoing relevance, and future trajectories of EEG in epilepsy research. We describe traditional approaches to record brain electrical activity and discuss novel cutting-edge, large-scale techniques using micro-electrode arrays. Contemporary EEG studies explore brain potentials beyond the traditional Berger frequencies to uncover underexplored mechanisms operating at ultra-slow and high frequencies, which have proven valuable in understanding the principles of ictogenesis, epileptogenesis, and endogenous epileptogenicity. Integrating EEG with modern techniques such as optogenetics, chemogenetics, and imaging provides a more comprehensive understanding of epilepsy. EEG has become an integral element in a powerful suite of tools for capturing epileptic network dynamics across various temporal and spatial scales, ranging from rapid pathological synchronization to the long-term processes of epileptogenesis or seizure cycles. Advancements in EEG recording techniques parallel the application of sophisticated mathematical analyses and algorithms, significantly augmenting the information yield of EEG recordings. Beyond seizures and interictal activity, EEG has been instrumental in elucidating the mechanisms underlying epilepsy-related cognitive deficits and other comorbidities. Although EEG remains a cornerstone in epilepsy research, persistent challenges such as limited spatial resolution, artifacts, and the difficulty of long-term recording highlight the ongoing need for refinement. Despite these challenges, EEG continues to be a fundamental research tool, playing a central role in unraveling disease mechanisms and drug discovery.
Keywords: EEG; Epilepsy; Seizures; mozek; epilepsie; analysis; Humans; záchvaty; komorbidita; lidé; elektroencefalografie; zvířata; mechanisms; Comorbidity; preclinical; Brain; animal models; Electroencephalography; Animals; high‐frequency oscillations; genetic epilepsies